Komunikasi Politik Dewan Pimpinan Cabang Partai Keadilan Sejahtera (DPC PKS) dalam Rekrutmen Kader di Medan Denai - Saripuddin, M.; Ritonga, Elfi Yanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The purpose of this research is to determine the political communication of the Prosperous Justice Party Branch Leadership Council (DPC PKS) in cadre recruitment in Medan Denai. This research uses qualitative methods with a field study approach. This research is a descriptive analysis study. Data sources for this research include primary data obtained through interviews and documentation, and secondary data originating from journal articles, books and relevant research. Data collection was carried out using semi-structured interview techniques and documentation studies. Data analysis follows the Miles and Huberman scheme, involving the process of data reduction, data presentation, and data verification. The results of this research indicate that the recruitment pattern for PKS DPC Medan Denai cadres involves three main approaches: open recruitment, internal selection, and informal approaches. In open recruitment, political communication is used to introduce the party's vision, mission and values to prospective cadres, build interest and encourage participation in the recruitment process. In internal selection, political communication helps explain new roles and responsibilities to potential cadres through dialogue, maintaining commitment and stability of party leadership. In the informal approach, political communication is personal and relies on personal relationships and trust, helping to motivate prospective cadres to join the party and contribute actively.